ChemInform Abstract: Two New Chemical Constituents from Leaves of Perilla frutescens var. acuta. Issue 2 (January 2015) - Woo, Kyeong Wan; Han, Ji Young; Suh, Won Se; Lee, Jei Hyun; Lee, Kang Ro
Abstract isolation and structure of two new compounds, perillascens (I) and perillaside (II), along with 34 known compounds